The economy of creative culture in an area with a high density of operators in the sector: the Marche of crafts and SME - Di Ferdinando, Gabriele; Dini, Giovanni (Piccola Impresa / Small Business, 2019)
This study aims to contribute to clarify the size and the potential of the creative and cultural industry in the socio-economic system. We consider the recent debate on the economic role of the cultural and creative activities in Italy and we analyze constraints and potential of the sector on the basis of a study conducted among operators of an representative area: the Marche region. This region is among the first in Italy for intensive presence in the sector and its weight in the economy. The analysis that has emerged has been used for a pilot project which aims to highlight the connections between crafts and cultural heritage.